Hubungan Respon Time Perawat dengan Tingkat Kepuasan Pasien di Instalasi Gawat Darurat RS Charlie Hospital Kendal - Devy Dwi Syavitri; Heny Prasetyorini (Pusat Riset dan Inovasi Nasional, 2025)
Response time refers to the speed of nurses in providing initial responses to patients, measured from the moment patients arrive at the hospital entrance until they receive medical attention from emergency room staff. Patient satisfaction is an important indicator of healthcare quality, reflecting the comparison between patient expectations and the services received. This study passed the ethical review process with approval number 66/EC-LPPM/UWHS/IV-2025 and used a quantitative correlational design with a cross-sectional approach. The sampling technique applied purposive sampling involving 197 respondents. Data were collected using a nurse response time observation sheet and a patient satisfaction questionnaire that had undergone validity and reliability testing. The validity test using the Pearson Product Moment method showed that the calculated r value was greater than the r table value of 0.361, indicating that all questionnaire items were valid. The reliability test using Cronbach’s alpha produced a coefficient value of 0.855, confirming that the instrument was reliable. Data analysis used univariate and bivariate analysis with the Spearman’s rho test. The results showed that nurse response time was categorized as fast (≤ 5 minutes) for 177 respondents (89.8%). Patient satisfaction levels showed that 177 respondents (89.8%) were very satisfied, 10 respondents (5.1%) were satisfied, and 10 respondents (5.1%) were moderately satisfied. The Spearman Rank test produced a p-value of 0.000 (<0.05) with a correlation coefficient of 0.893, indicating a strong and positive relationship between nurse response time and patient satisfaction in the Emergency Room of Charlie Hospital Kendal.